Deformation Bands and Associated FIP Characteristics From High-Porous Triassic Reservoirs in the Tarim Basin, NW China: A Multiscale Analysis - Yan, Wenyuan; Zha, Ming; Qu, Jiangxiu; Ding, Xiujian; Zhang, Qinglan (Frontiers in Earth Science, 2021)
Deformation bands are widely formed and distributed in Triassic high-porous rocks as a result of multistage tectonic movement. In this research, core observation, the rock thin section (fluorescence and casting thin section), FIB-SEM, X-ray diffraction, Raman laser, and thermometry of fluid inclusions were employed to describe the macro- and micro characteristics of deformation bands and their associated relationship with microfractures. Results indicate that the main types of deformation bands formed in the Lunnan Triassic high-porosity sandstone during the Yanshanian and Himalayan periods under different temperature and pressure conditions are compaction shear bands, and their quantity increases evidently with the distance of thrust faults. The density of deformation bands near the fault is about 15/m; porosity and permeability decrease sharply compared with those of the host rock. Microscopically, two obtained fluid-inclusion planes (FIPs) can be distinguished as 51 samples collected from 12 wells by the cutting relationship and mechanical characteristics. The homogenization temperature of associated aqueous inclusion is generally characterized by two peaks, mainly 70–80°C and 110–120°C, which were formed in the Late Yanshanian and Late Himalayan periods. The formation period of deformation bands induced by the intragranular microfractures improved the reservoir seepage capacity. In the later stage, as the interlayer and barrier with low porosity and low permeability affects the distribution of oil and gas, which is an important factor in this study of the local fluid dynamic field and high-quality reservoir evolution distribution.